Preliminary effects of parent-implemented behavioural interventions for stereotypy. (3rd May 2016) - Lanovaz, Marc J.; Rapp, John T.; Maciw, Isabella; Dorion, Catherine; Prégent-Pelletier, Émilie
Abstract: Objective : The purpose of our study was to replicate and extend previous research on using multicomponent behavioural interventions designed to reduce engagement in stereotypy by examining their effects when implemented by parents over several months. Methods : We used an alternating treatment design to examine the effects of the parent-implemented interventions on engagement in stereotypy and appropriate behaviour in three children with autism and other developmental disabilities. Results : The parent-implemented multicomponent treatments reduced vocal stereotypy in all three participants and increased engagement in appropriate behaviour in two participants. These effects persisted up to 24 weeks following the parent training sessions. Conclusions : Altogether, our preliminary results support (a) the involvement of parents as behaviour change agents to reduce engagement in stereotypy and (b) the scheduling of regular, but infrequent (i.e. weekly to monthly), follow-up meetings to monitor the effects of behavioural interventions in outpatient and home-based service delivery models.